1999
DOI: 10.1034/j.1600-051x.1999.t01-5-261101.x
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal human serum antibody responses to outer membrane antigens of Actinobacillus actinomycetemcomitans

Abstract: We hypothesize that serum antibody responses to antigens of a periodontopathogen would vary temporally and that the specificity of these host antibodies would relate to infection and disease activity. To test the hypothesis, we obtained between 6 and 13 serum samples from Actinobacillus actinomycetemcomitans (Aa)-positive (serological and microbiological) periodontitis patients at time points between 18 and 42 months into the study, and evaluated specific antibody responses to outer membrane antigens (OMA) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Therefore these elevations cannot be attributed to secondary effects of the AD disease process, such as poor nutrition or other dementia-related neglect. While it could be suggested that the antibody to these oral pathogens may have been cross-reactive with antigens from other sources, the literature is replete with studies supporting the specificity of these antibodies for oral infections [2021, 43–46], and that successful treatment and maintenance of periodontitis significantly lowers these antibody levels [47]. Comparison of these antibody levels to those described in numerous populations show levels in the AD and MCI subjects in the current study to be similar to chronic periodontitis patients [4549].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore these elevations cannot be attributed to secondary effects of the AD disease process, such as poor nutrition or other dementia-related neglect. While it could be suggested that the antibody to these oral pathogens may have been cross-reactive with antigens from other sources, the literature is replete with studies supporting the specificity of these antibodies for oral infections [2021, 43–46], and that successful treatment and maintenance of periodontitis significantly lowers these antibody levels [47]. Comparison of these antibody levels to those described in numerous populations show levels in the AD and MCI subjects in the current study to be similar to chronic periodontitis patients [4549].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated serum antibody responses to some outer membrane proteins of A. actinomycetemcomitans [11,12]. Principal putative virulence determinants of A. actinomycetemcomitans include the leukotoxin, a cytolethal toxin, the cell wall lipopolysaccharide, and fimbria [3,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Principal putative virulence determinants of A. actinomycetemcomitans include the leukotoxin, a cytolethal toxin, the cell wall lipopolysaccharide, and fimbria [3,[13][14][15][16]. Moreover, several outer membrane proteins have been recorded as immunogenic at the molecular level, such as RcpA, a 43-kDa protein, which is similar to precursor protein D of the general secretion pathway of Gram-negative bacteria and genetically related to fimbria-associated proteins [17], AaPAL, a 17 kDa protein, which has been identified as a highly immunoreactive peptidoglycan-associated lipoprotein [12], Omp34, a protein belonging to the OmpA family [18][19][20], and the heat-modifiable Omp16 [11,21]. Studies using in vivo induced antigen technology (IVIAT) [22] have the potential to identify large numbers of immunogenic antigens.…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of acute-phase proteins have been identified in adult periodontitis patients and appear to reflect both the infection and the acute and chronic inflammation that exists in the periodontium (18,39,55). At the same time, it is clear that a serum antibody response to these localized infections exists and that it results from specific elicitation of antibody to an infecting microorganism (19,24,40,41,46,79).Periodontal disease has been effectively used as a model of host-bacterium interactions, inflammation, and chronic inflammatory diseases, particularly for the ability to longitudinally describe bacterial and host factors in the oral cavity and to correlate changes in these factors with pathological changes in …”
mentioning
confidence: 97%